2020
DOI: 10.1136/bcr-2019-232304
|View full text |Cite
|
Sign up to set email alerts
|

Case of small bowel perforation secondary to nivolumab and ipilimumab related tumour regression

Abstract: A 56-year-old man undergoing immunotherapy treatment for metastatic melanoma presented with sudden onset testicular pain radiating into his abdomen. On examination, the abdomen was generally tender with associated guarding. Imaging revealed a perforation of the small bowel at the site of a metastatic lesion. Histology revealed that this process was non-inflammatory in nature. A diagnosis of small bowel perforation secondary to immunotherapy driven rapid tumour regression was made. The patient was treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The case revealed the large spectrum of immune-related adverse effects that can even be missed or diagnosed by chance [45]. Another interesting side effect involving the small bowel was reported in a 56-year-old patient with metastatic melanoma, under treatment with nivolumab and ipilimumab, who developed small bowel perforation due to fast tumor regression after immunotherapy, revealing the multitude of possibilities when it comes to ICI related adverse effects [46]. We found other four cases of nivolumab, ipilimumab or atezolizumab treated patients that developed small bowel perforation due to ICI treatment that were also reported in the literature [47][48][49][50].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The case revealed the large spectrum of immune-related adverse effects that can even be missed or diagnosed by chance [45]. Another interesting side effect involving the small bowel was reported in a 56-year-old patient with metastatic melanoma, under treatment with nivolumab and ipilimumab, who developed small bowel perforation due to fast tumor regression after immunotherapy, revealing the multitude of possibilities when it comes to ICI related adverse effects [46]. We found other four cases of nivolumab, ipilimumab or atezolizumab treated patients that developed small bowel perforation due to ICI treatment that were also reported in the literature [47][48][49][50].…”
Section: Discussionmentioning
confidence: 92%
“…A case of asymptomatic appendicitis after dual therapy (nivolumab and ipilimumab) therapy [45] diagnosed through a routine positron emission tomography (PET) pointed out the specter of immune related events that can be missed or only diagnosed by chance; another interesting case described a small bowel perforation due to fast tumor regression secondary to nivolumab and ipilimumab treatment [46]. Other four cases of patients under nivolumab, ipilimumab or atezolizumab therapy developed small bowel perforation, a rare, but potentially fatal event [47][48][49][50].…”
Section: Gastrointestinal Tract Toxicitymentioning
confidence: 99%
“…Enterocolitis associated with immunotherapy has an incidence of 2.0%[ 28 ], which increases to 40.0% in patients on ipilimumab[ 29 ], and usually develops after 6-7 wk of treatment. Bowel perforation and death occur respectively in 1.0% and 0.8% of patients[ 27 - 31 ].…”
Section: Enterocolitismentioning
confidence: 99%
“…Intestinal perforation after immunotherapy is a rare event (Figure 6 ). A case report by Patel et al [ 31 ] described a jejunal perforation after treatment with ipilimumab and nivolumab for metastatic melanoma, related to tumor regression. Another paper by Romano et al [ 65 ] reported a small bowel perforation in a patient treated with nivolumab for metastatic lung cancer.Radiofrequency or micro-wave ablation can cause injuries to nearby organs.…”
Section: Perforationmentioning
confidence: 99%
“…A similar phenomenon (of rupture associated with vemurafenib treatment) can occur in the case of the liver [ 135 ]. The rare possibility of immunotherapy causing non-inflammatory bowel perforations as a result of rapid tumor regression, is an important aspect of the medical literature [ 136 , 137 ], as the toxicity of immune checkpoint inhibitors like ipilimumab and nivolumab is related to their clinical efficacy. Adjuvant high-dose ipilimumab administered after ipilimumab and nivolumab for inoperable metastatic disease [ 138 ] were also reported.…”
Section: Main Findings Of the Literature (Review) Questmentioning
confidence: 99%